A C-type lectin TcCTL1 is required for embryogenesis in Tribolium castaneum. (February 2023) - Zhang, Yonglei; Zhang, Ping; Yu, Runnan; Li, Bin
Abstract: C-type lectin S group (CTL-S) plays a variety of roles in invertebrate including pathogen recognition and activation of immune responses. Previous studies have shown that CTL-S subfamily of Tribolium castaneum is mainly divided into two clades, of which only TcCTL1 was separately located in one clade. However, it remains unclear whether TcCTL1 occurs the differentiation of function. Therefore, the CTL-S TcCTL1 gene was cloned and characterized from T. castaneum . Functional analysis revealed that TcCTL1 could recognize and agglutinate pathogens, as well as activate immune signaling pathways to participate in immune response, which was consistent with our previously reported for TcCTL5 and TcCTL6 . Differently, RNAi of TcCTL1 discovered that the egg produced by ds TcCTL1- treated adult could not hatch into larvae. Further DAPI-straining embryo indicated that the process of embryogenesis in ds TcCTL1 -treated beetle was defeated, implying that TcCTL1 is required for embryogenesis in T. castaneum except for immune response. These results will aid implications for the understanding of CTL-S in invertebrate. Highlights: First report of TcCTL1 involved in embryogenesis except for immune response.